The Logic of Practicality: An Inquiry into the Nature of the EU’s Practice of International Peace Mediation - Cupać, Jelena; Ružić, Maja (Journal of Regional Security, 2018)
In the paper, the authors use the practice approach to untangle the nature of the EU’s practice of international peace mediation (IPM). Drawing on the recent practice turn in international relations scholarship, Bourdieu’s well-known concept of habitus is employed in order to elicit the background knowledge and values that constitute and transform this practice. In this regard, the EU’s practice of international peace mediation is examined through the lens of general peace mediation norms, as well as through the rules, norms, identity and culture that are specific to the European Union. Three cases are used for this endeavor: (1) the EU support for the Aceh peace process in Indonesia (2004–2008); (2) the EU engagement in the Russian- Georgian war (2008–2012); and (3) the mediating role which the EU has undertaken in the recent dialogue between Kosovo and Serbia (2011–2013).